Silvopastoral systems with native forage species and their impact on milk production and quality : a case study on a farm in the Colombian Amazonian foothills (2025)
This study compared a silvopastoral sys-tem (SPS) with promising shrub and tree species against a traditional grazing system (TS) in the Ama-zonian foothills of Colombia, evaluating milk production and composition, dry matter intake (DMI), and economic performance. A crossover design was applied with 10 lactating gyr×holstein crossbreed cows. Dry matter intake, milk production and feed efficiency were significantly greater (p<0.001) in the SPS (12.90 kg DM/day, 14.13 kg/cow/day, and 1.24 milk kg/kg DM) compared to TS (10.5 kg DM/day, 12.92 kg/cow/day, and 1.17 kg milk kg/kg DM) respectively. Although milk composition did not dif-fer (p>0.05) between systems, milk urea nitrogen (MUN) was greater in the SPS (11.9 vs. 10.2 mg/dL; p<0.001), which reflects a greater protein intake consistent with the forage composition provided by this system. The SPS required a greater initial invest-ment (USD 2240.85 vs. USD 501.62), resulting in a 4.08% increase in the production cost per kilogram of milk (USD 0.37 vs. USD 0.36). Nevertheless, the SPS demonstrated greater profitability, with a benefit-to-cost ratio (B/C) of 2.05, a greater net present value, and a shorter payback period (3.5 years). These results, highlight the potential of SPS as an effective strategy for improving dairy productivity and feed efficiency while mitigating environmental pressures in tropical livestock systems.